High gain compact antenna design for underwater communication - Majeed, Sama Fouad (2017)
Nowadays, communications technology is developing rapidly and becoming more advanced each day. In turn, the demand for this technology is also increasing. Underwater communication is not an exception; it has received the attentions of scientists working in the communications and telecommunication field. Two types of waves have been used in underwater communications and systems mostly. These are known as electromagnetic and sonar waves. Research findings show that electromagnetic waves yield more promising results when submerging communication devices in water. However, electromagnetic wave applications have also issues on it is own to address. The performance of electromagnetic waves degrades exponentially when submerged in a medium such as water. Due to this reduction in wave energy, many hubs and transceivers should be used to cover an area for transferring data from one station to the other. In addition, the demand for free licensed frequency bands such as industrial scientific and medical (ISM) and wireless local area network (WLAN) has forced users to require more band width (BW) and a higher data transfer rate. Thus, higher frequency bands such as microwave (MW) frequency bands are required. However, higher bands than microwave bands also degrade in water, where the wave distance will become too short. Hence, a higher data transfer rate and smaller dimensions of the microwave instruments are required for underwater communications compared to electromagnetic waves in a lower band, sonar and ultra-sonic waves, and microwave, which can be a promising technology to apply for submerged communications.A compact-sized high gain photonic band gab (PBG) structure stack antenna resonating at 2.4 GHz and also a compact high gain ultra wide band antenna (UWB) resonating at (1.65–6.8) GHz for ISM band and WLAN are presented in this thesis. Simulation and measurement results have been investigated and then the behaviour of the antennas on the reflection coefficient, antenna pattern and gain are also studied. The proposed microstrip antenna is designed at 2.4 GHz, achieving a miniaturized size by almost 20%, a higher gain, and higher efficiency at the desired harmonics in air and water compared to similar previous experiments. However, not many antennas have been designed for underwater communications and most are quite bulky. The performance of the antenna submerged in water was measured in three ways: with both antennas submerged in water, one at the surface, and the other inserted in water, followed by depth valuation. When both are submerged in water, the reflection coefficient is shifted to a lower frequency band (0.86 GHz) with an increase in distance between the antennas. The proposed antenna is working at an ISM lower band (0.91 GHz) when both are in water. Besides that, at distances of more than 350 mm, some more resonances occur at 1.5 GHz, 1.8 GHz, and even 2.4 GHz at 500 mm distance. The depth variation of the antenna was performed in a depth from 3–25 cm. The same procedure is applied to the UWB antenna for measurement in water. When the antennas are inserted in water or even face the water, the broad BW of the antennas is degraded, especially at higher frequencies higher than 4 GHz. There is not much of a difference between the measurements when both are positioned in water and when one is put on the surface only. However, keeping one antenna on the surface and inserting another in the water can cause the antennas to resonate like three-band antennas working at lower bands. The differences between them occur when both antennas are inserted and one at the surface is the middle band. The middle band is more effective when both antennas are inserted in water and degraded with distance increment. For future work and further studies in underwater communications, the size of the testing medium can be increased. Thus, further distances can be considered in the testing procedure and investigations. Besides that, the number of antenna arrays can be increased to achieve increased range of transmitted data.